A bibliographical study on the works of Sayyid Abul A’la Mawdudi - Abul Kalam Mohammad Shahed (Penerbit Universiti Kebangsaan Malaysia, 2001)
Sayyid Abul A’la Mawdudi (1903-79) was an outstanding Islamic thinker and socio-political and religious reformer of the twentieth century. He held a modernist outlook but within the confine of Shari’ah values. He was a gifted and prolific writer. He had been considered as one of the most widely read Muslim writers. His writings extended to over hundred books, hundreds of pamphlets and innumerable articles, speeches and intrviews. He had a unique style of writing, which fully reflected his deep and vast knowledge. His books have been translated into the major languages of the world. The subjects covered by his writings include a wide range of disciplines such as tafsir, Hadith, religion, law, philosophy, history, politics, economics, sociology, science, literature, ethics and education, and all have received a due share of his attention. This study is an effort to present all available works of Mawdudi in accordance with the subject matters followed by a brief introduction wherein it is necessary